Bacterial profile and antimicrobial resistance patterns of bloodstream infections at Amhara Public Health Institute, Bahir Dar, Ethiopia - Michael Getie; Wudu Tafere; Alem Tsega; Tsehaynesh Gebreyesus; Gizeaddis Belay; Hailu Getachew; Yosef Gashaw; Aimro Tadese; Tigist Birku; Tigabu Birhan; Alemayehu Abate; Teshiwal Deress; et al. (PLoS ONE, 2026)
Background Managing bloodstream infections in resource-constrained regions like Ethiopia is challenging due to scarce blood culture surveillance data. To guide empirical therapy, this study determines the bacterial profiles and antimicrobial resistance patterns among patients with suspected bloodstream infections at the Amhara Public Health Institute. Methods This retrospective study analyzed blood culture records from the Amhara Public Health Institute spanning January 1, 2020, to December 30, 2023. Blood samples were processed using standardized manual culture techniques in accordance with World Health Organization (WHO) protocols. Antimicrobial susceptibility testing was performed using the Kirby-Bauer disk diffusion method following Clinical and Laboratory Standards Institute (CLSI) guidelines. Statistical analysis was conducted using SPSS version 20, employing descriptive statistics and regression models, with statistical significance defined as p < 0.05. Results True bacterial pathogens were isolated from 50.3% (N = 340) of the 676 patients, with Gram-negative bacteria predominating (61.2%, N = 208) over Gram-positive bacteria (38.8%, N = 132). Notably, ESKAPEE pathogens accounted for 96.5% (N = 328) of all isolates, led by Klebsiella spp. (25.9%, N = 88), Enterococcus spp. (20.9%, N = 71), and S. aureus (15.6%, N = 53). Among Gram-positive isolates, high resistance was observed against oxacillin (74.5%, N = 41), penicillin (72%, N = 36), and vancomycin (51.1%, N = 24). Gram-negative isolates exhibited critical resistance to national frontline therapeutics, including ampicillin (100%, N = 24), ceftriaxone (92.4%, N = 157), and trimethoprim-sulfamethoxazole (89.4%, N = 126). Overall, multidrug-resistant (MDR), extensively drug-resistant (XDR), and pandrug-resistant (PDR) profiles were detected in 43.8% (N = 149), 30.5% (N = 104) and 5.3% (N = 18) of isolates with similar distributions observed among ESKAPEE strains. Sex and age were the only independent predictors of culture positivity, with female sex reducing bloodstream infection odds by 44% (p = 0.002). Conversely, neonates (≤ 28 days) and young adults (15–24 years) had 4.7 times (p = 0.001) and 9.5-times (p = 0.001) higher odds compared to elderly patients. Conclusions This study reveals a severe 50.3% (N = 340) bloodstream infection rate dominated by highly resistant Gram-negative and ESKAPEE pathogens, disproportionately affecting males, neonates, and young adults. Combating this threat requires immediate antibiotic stewardship, updated guidelines, and advanced laboratory testing (anaerobic culture, minimum inhibitory concentration, and molecular sequencing) to track and manage resistance.